2019
DOI: 10.7202/1057965ar
|View full text |Cite
|
Sign up to set email alerts
|

Fee-Paying English Language Learners: Situating International Students’ Impact on British Columbia’s Public Schools

Abstract: This article examines the relationship between international education and English as an additional language (EAL) education in British Columbia’s public education system. Drawing on a wide range of data generated as part of a longitudinal study of high school aged fee-paying international students (FISs) in an urban school district in British Columbia, I make the case that FIS recruitment and presence is having a socializing impact on EAL education in British Columbia’s public schools. In contrast to the way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Furthermore, competition for fee-paying students has exacerbated geographic inequality within the province's public education sector (Poole et al, 2020). Deschambault (2019) has cited policy distinctions between fee-paying international students and other ELLs as a factor contributing to the commodification of English Language Learning in British Columbia. Also researching the British Columbia context, Cover (2016) concluded that a lack of critical attention to the marketization of education in the local Bell et al media can be explained by the "dominance of marketization and associated neoliberal values already saturating the public sphere " (p.193).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, competition for fee-paying students has exacerbated geographic inequality within the province's public education sector (Poole et al, 2020). Deschambault (2019) has cited policy distinctions between fee-paying international students and other ELLs as a factor contributing to the commodification of English Language Learning in British Columbia. Also researching the British Columbia context, Cover (2016) concluded that a lack of critical attention to the marketization of education in the local Bell et al media can be explained by the "dominance of marketization and associated neoliberal values already saturating the public sphere " (p.193).…”
Section: Introductionmentioning
confidence: 99%
“…Their limited life experience, and levels of maturity and development intertwine with immediate demands for learning in a new environment (Cheng & Yang, 2019), compounded by the lack of local social support and particularly the lack of peer connections (Kim & Okazaki, 2014; Walsworth et al, 2021). Some students do not have appropriate preparation for navigating local secondary educational systems, leading to challenges for academic and psychosocial adaptation (Deschambault, 2018; Kuo & Roysircar, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Canadian schools have seen a steady increase in English language learners (ELLs) over the past decades (Cummins & Persad, 2014;Duff , 2007), more so recently due to the growing number of international students (Deschambault, 2018). In British Columbia, alongside pull-out sheltered English language classes, students learning English as an additional language (EAL) are generally integrated into mainstream content classrooms (Gunderson, D'Silva, & Murphy Odo, 2014), requiring that all teachers have some knowledge about and are open to linguistically and culturally responsive teaching approaches .…”
Section: Introductionmentioning
confidence: 99%